Effects of Different Ingredients on the Flavor Formation of Luosi Soup - Chunyou LIU; Jing QIU; Shujun WANG; Chaomin YIN; Hua LIN; Xian'e REN; Xiangyi TANG; Yongchun HUANG (Shipin gongye ke-ji)
In order to investigate the effects of different ingredients such as Luosi meat, pork bones, chicken skeleton and spices on the flavor formation of Luosi soup, the physio-chemical characteristics and flavor components of Luosi soup were determined using spectroscopic techniques, gas chromatography (GC), high performance liquid chromatography (HPLC) and gas chromatography-mass spectrometry (GC-MS). The results showed that the different ingredients had a significant effect on the water-soluble protein content, average particle size and polydispersity index of Luosi soup, but the different ingredients had no significant effect on the Zeta potential of Luosi soup. The results of GC showed that pig bone and chicken skeleton were the main sources of oleic, linoleic, palmitic acid and palmitoleic acids in Luosi soup. The results of GC-MS indicated that a total of 35 volatile flavor compounds, including 10 aldehydes, 4 alcohols, 11 olefins, 1 alkane, 2 ketones, 2 esters, 2 ethers and 3 phenols, were identified in Luosi soup. The aroma activity values indicated that anethole, estragole, eucalyptol and nonanal were the key volatile compounds in Luosi soup, among which the anethole and eucalyptol were derived from spices, while nonanal was originated from Luosi meat, pork bones and chicken skeleton, and these volatile compounds conferred sweet, anise, fatty and citrusy flavor to the Luosi soup. The results of amino acid analysis showed that free amino acids, including glutamic acid, aspartic acid, glycine and alanine, were the important flavor amino acids in Luosi soup, and 5'-GMP, 5'-AMP and 5'-IMP, were the main umami nucleotides, these flavor amino acids and nucleotides together conferred sweet and umami taste characteristics to Luosi soup, and these flavor compounds mainly originated from Luosi meat, pork bones and chicken skeleton. In conclusion, animal-based meat ingredients and plant-based spices together constituted the characteristic aroma and taste of Luosi soup.